Kinerja Bank Indonesia Dalam Pelaksanaan Pengawasan Kegiatan Usaha Penukaran Valuta Asing Bukan Bank (Money Changer) Di Kabupaten Badung - Setia, Ari Indra; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2020)
Badung regency is in the first place with the most Money Changer business in Bali, which is 446 units or about 70% of the total money changer business in Bali. The implementation of its activities are still encountered problems such as unlicensed Money Changer and the existence of fraud related to money changer business. The purpose of this research is to determine the performance of Bank Indonesia that has authority in carrying out supervision system of non-bank foreign exchange business activities. Data is collected by observation method, semistructure interview and documentation. Based on the research, the results showed that there are several indicators that have been well met as well as indicators of Productivity, Accountability, Service Quality, and Responsibiltas. While the Responsiveness indicator shows good results but is not optimal, due to lack of socialization, direct supervision, and human resources. Keywords: Performance, Money Changer, Supervision, Foreign Exchange.